Association Between Extremely Preterm Cesarean Delivery and Maternal Depressive and Anxious Symptoms: A National Population-based Cohort Study. Issue 4 (22nd December 2021) - Blanc, J.; Resseguier, N.; Lorthe, E.; Goffinet, F.; Sentilhes, L.; Auquier, P.; Tosello, B.; d'Ercole, C.
Abstract : ( BJOG . 2021;128:594–602) During the postpartum period, women are at high risk of developing depression and anxiety. Risk factors that may contribute to the development of these conditions are preterm birth and cesarean delivery (CD). In this context, extremely preterm deliveries, usually associated with emergency CD, is an important area of study. The aim of this study was to examine whether there was an association between CD at <26 weeks' gestation and maternal depression and anxiety. The authors hypothesized that cesarean delivery before 26 weeks' gestation compared to delivery between 26 and 34 weeks would be associated with severe depression or anxiety.